Impact of Agricultural Sectors and Income Inequality in Rural Toward Role of Public Education in Decreasing Educational Inequality in Indonesia - Bahari, Doddy Ismunandar; Siregar, Hermanto; Sahara, Sahara; Rachman, Handewi Purwati Saliem (International Journal of Economics and Financial Issues, 2019)
Generally, the aims of this research was to analyze the role and the inputs allocation of public education and the factors which affected educational inequality. Using panel data in 33 provinces during 2010 to 2016 which then analyzed by stochastic frontier method. The results showed excessive allocation of resources in the addition of school buildings at primary and junior secondary school. Reducing education inequality could be encouraged through the addition government spending on education, number of teachers in junior secondary education and lecturer in higher education, and number of school buildings in senior secondary school and college education. The role public education performance was only able to affect 83.8 of educational inequality, and its remaining 16,2 percent due to the high percentage of rural school age labor, percentage of labor in the agricultural sector, farmer’s terms of trade, and gross domestic product per labor on the agricultural sector. Keywords: education inequality, public education, agricultural sector, income inequality JEL Classifications: I24, H41, Q19, D63 DOI: https://doi.org/10.32479/ijefi.6924